Process of technical stabilization of gastric endoscopic submucosal dissection at the National Cancer Center in Japan - Suzuki, Haruhisa; Oda, Ichiro; Sekiguchi, Masau; Abe, Seiichiro; Nonaka, Satoru; Yoshinaga, Shigetaka (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Endoscopic submucosal dissection (ESD) was originally developed in 1995 using an insulation-tipped diathermic knife (Olympus, Tokyo, Japan) to achieve en-bloc resection of early gastric cancer (EGC). It has been suggested that advances in endoscopic devices and medical equipment, such as the high-frequency generator (1999) and hemostatic forceps (2000), and procedural improvements including post-ESD preventive coagulation of visible vessels in the resection area (2003) led to further progress of ESD; therefore, we investigated the actual process of technical stabilization of gastric ESD. Materials and Methods: A total of 1,713 consecutive patients with solitary differentiated-type EGC at initial onset underwent ESD at our hospital from 1995 to 2006. We retrospectively assessed ESD outcomes for all patients by dividing them into three chronological periods: 1995-1998 (1st period; 57 patients), 1999-2002 (2nd period; 563 patients), and 2003-2006 (3rd period; 1,093 patients). Results: The en-bloc resection, intraoperative bleeding, and delayed bleeding in the 1st/2nd/3rd period were 52.6%/94.7%/99.3% (1st vs. 2nd, p<0.01; 2nd vs. 3rd, p<0.01), 8.8%/7.1%/1.6% (1st vs. 2nd, no significant difference; 2nd vs. 3rd, p<0.01), and 15.8%/7.6%/3.3% (1st vs. 2nd, p<0.05; 2nd vs. 3rd, p<0.01), respectively. Conclusion: Gastric ESD has stabilized technically following advances in endoscopic devices and medical equipment together with procedural improvements.